2018
DOI: 10.1111/jcmm.13806
|View full text |Cite
|
Sign up to set email alerts
|

The lysine acetyltransferase GCN5 contributes to human papillomavirus oncoprotein E7‐induced cell proliferation via up‐regulating E2F1

Abstract: General control nondepressible 5 (GCN5), the first identified transcription‐related lysine acetyltransferase (KAT), is an important catalytic component of a transcriptional regulatory SAGA (Spt‐Ada‐GCN5‐Acetyltransferase) and ATAC (ADA2A‐containing) complex. While GCN5 has been implicated in cancer development, its role in cervical cancer is not known. The human papillomavirus (HPV) oncoprotein E7 abrogates the G1 cell cycle checkpoint and induces genomic instability, which plays a central role in cervical car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 76 publications
2
16
0
Order By: Relevance
“…We have demonstrated that both WDHD1 and GCN5 play key roles in S-phase entry and G1 checkpoint control in E7 expressing cells [16,19], and our data suggest that WDHD1 regulates GCN5 expression ( Figs. 1 and 2).…”
Section: Overexpression Of Gcn5 Overrides G1 Checkpoint Activation Ansupporting
confidence: 57%
See 3 more Smart Citations
“…We have demonstrated that both WDHD1 and GCN5 play key roles in S-phase entry and G1 checkpoint control in E7 expressing cells [16,19], and our data suggest that WDHD1 regulates GCN5 expression ( Figs. 1 and 2).…”
Section: Overexpression Of Gcn5 Overrides G1 Checkpoint Activation Ansupporting
confidence: 57%
“…Our previous study demonstrated a role for WDHD1 in G1 checkpoint abrogation E7 expressing cells [ 16 ]. It was reported that GCN5 plays a role in the G1 checkpoint control while WDHD1 inhibits its degradation [ 17 19 ]. Moreover, our recent study revealed that GCN5 also promotes cell cycle progression in HPV E7 expressing cells [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, E2F1 has a synergistic effect with c-Myc. E2F1 has been confirmed as a target gene of c-Myc, which can reduce the expression of c-Myc by down-regulating E2F1, thereby inhibiting the proliferation of tumor cells [27]. The results of this study showed that the protein levels of c-Myc, E2F1 and NF-κB in BGC-823 cells decreased after PN treatment.…”
Section: Discussionmentioning
confidence: 60%